THE USE OF PODCASTS TO IMPROVE LISTENING SKILLS IN EFL CLASSROOMS - Rafidhah Hanum; Fakhrul Rijal; Muhammad Zulhairi Bin Zubairi (SENSEI RESEARCH CENTER, 2025)
Listening is a difficult skill for EFL students because they rarely hear English outside the classroom. Nowadays there are many podcasts that can be listened to for free through the smartphone. This article discusses the use of podcasts to improve listening skills in EFL classrooms. The method used is literature review from various journals. The result shows that podcasts can improve the listening skills of the students because they can listen many times and also anywhere. However, the teacher must choose the podcast that is suitable with the level of the students. So, podcasts are good to be used in the listening class.